Superresolution microscopy reveals linkages between ribosomal DNA on heterologous chromosomes - Potapova, Tamara A. (J Cell Biol, 2019)
The spatial organization of the genome is enigmatic. Direct evidence of physical contacts between chromosomes and their visualization at nanoscale resolution has been limited. We used superresolution microscopy to demonstrate that ribosomal DNA (rDNA) can form linkages between chromosomes. We observed rDNA linkages in many different human cell types and demonstrated their resolution in anaphase. rDNA linkages are coated by the transcription factor UBF and their formation depends on UBF, indicating that they regularly occur between transcriptionally active loci. Overexpression of c-Myc increases rDNA transcription and the frequency of rDNA linkages, further suggesting that their formation depends on active transcription. Linkages persist in the absence of cohesion, but inhibition of topoisomerase II prevents their resolution in anaphase. We propose that linkages are topological intertwines occurring between transcriptionally active rDNA loci spatially colocated in the same nucleolar compartment. Our findings suggest that active DNA loci engage in physical interchromosomal connections that are an integral and pervasive feature of genome organization.